Theater and Catholicism: comparative dramaturgy exploration of plays by Albee, Leñero, and Chico de Assis - Batista dos Santos Hasmann, Robson (Árboles y Rizomas, 2024)
We propose a comparative analysis of plays written by playwrights from the United States, Mexico and Brazil, emphasizing the intertextuality of the plays with certain rites of Roman Catholicism. All the plays were written in the context of the Second Vatican Council, when the Catholic Church sought to bring its principles into line with the transformations taking place in the Western world during the 1960s and 1970s. The study, which falls within the scope of comparative dramaturgy (Betti, 2017), discusses the aesthetic procedures of the plays Who’s Afraid of Virginia Woolf? by Edward Albee (1977), Pueblo rechazado, by Vicente Leñero (2008), and Missa leiga, by Chico de Assis (n.d.) regarding the presence of some elements and rites of Catholicism in the construction of the dramatic action. Among the changes brought about by the Council, we highlight those involving the celebration of mass. We identified that the dialog with Catholicism is built on the social and political peculiarities of each country and, above all, according to the conditions of creation, production and dissemination of theatrical art in the respective contexts.